In Situ Investigation of the Oxidation of Cobalt‐Base Superalloys in the Environmental Scanning Electron Microscope1. Issue 8 (7th July 2015) - Weiser, Martin; Reichmann, Angelika; Albu, Mihaela; Virtanen, Sannakaisa; Poelt, Peter
Abstract Since their discovery in 2006, cobalt‐base superalloys have aroused increasing interest as potential materials for various high‐temperature applications. One of the still unsolved problems is their resistance to oxidation. In the present study, the very first stages of the oxidation process of a Co–9Al–9W alloy were investigated. To this aim, the progress of the oxidation process was continuously observed at high magnification in an environmental scanning electron microscope (ESEM). Oxidation starts not necessarily at the grain boundaries, and both the onset temperature and the oxidation rate depend on the crystallographic orientation of the crystallites.